Association of electrocardiographic patterns after successfully resuscitated out-of-hospital cardiac arrest with significant coronary lesions and mortality: a predefined substudy of the angiography after out-of-hospital cardiac arrest without ST-segment elevation (TOMAHAWK) trial : clinical investigation - Thevathasan, Tharusan; Claus, Julia; Roßberg, Michelle; Skurk, Carsten; Fichtlscherer, Stephan; Akın, Ibrahim; Fuernau, Georg; Hassager, Christian; Zeymer, Uwe; Preusch, Michael R.; Graf, Tobias; Feistritzer, Hans-Josef; et al. (Critical care medicine, 2025)
OBJECTIVES: - The use of electrocardiograms for predicting significant coronary lesions and mortality in patients with successfully resuscitated out-of-hospital cardiac arrest (OHCA) without ST-segment elevation has not been defined yet. The objective of this study was to investigate the association and predictive value of various standardized 12-lead electrocardiogram patterns in patients with successfully resuscitated OHCA and no ST-segment elevations on the presence of significant coronary lesions (diagnostic performance) and 30-day mortality (prognostic performance). - DESIGN: - Predefined subanalysis of the Angiography after Out-of-Hospital Cardiac Arrest without ST-Segment Elevation (TOMAHAWK) trial. - SETTING: - Multicenter, international randomized controlled trial across 31 centers. - PATIENTS: - Adult patients with successfully resuscitated OHCA and no ST-segment elevations. - INTERVENTIONS: - The first recorded electrocardiogram after the return of spontaneous circulation (ROSC) at hospital admission was analyzed by experienced physicians. - MEASUREMENTS AND MAIN RESULTS: - Significant coronary lesions and 30-day mortality. In total, 412 patients with a coronary angiography were included, of which 163 (40%) had significant coronary lesions. No electrocardiogram pattern was identified as a predictor of significant coronary lesions. In the total cohort of patients with and without coronary angiography, right bundle branch blocks (BBBs), prolonged intrinsicoid deflection times, and intrinsicoid deflections in right BBB were strong, independent predictors of 30-day mortality. The “intrinsicoid deflection” is the sharp upward deflection in the QRS complex of an electrocardiogram. The “intrinsicoid deflection time” is the interval from the start of the QRS complex to the peak of the R wave. The predictive performance for significant coronary lesions was poor across all electrocardiogram patterns and better for 30-day mortality. - CONCLUSIONS: - Standardized 12-lead electrocardiogram patterns after ROSC at hospital admission in patients with successfully resuscitated OHCA without ST-segment elevations have poor predictive performance for the presence of significant coronary lesions. Different QRS-related patterns might identify patients with higher risk of short-term mortality.